KELAYAKAN MEDIA ANIMASI SUBMATERI KOMPONEN EKOSISTEM DAN POLA INTERAKSI ORGANISME SMA MUHAMMADIYAH 2 PONTIANAK - Ruspandi, Ruspandi; Candramila, Wolly; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to compile and determine the feasibility of video-based learning media animation and described the students’ learning motivation in sub material of Ecosystem Components and Interaction Patterns among Organisms in 10th grade of high school students. The research form used was Development Research which included preliminary stage (analysis and design) and formative evaluation (self evaluation, expert review, one-to-one, small group, and field test). The samples of research used were 10th grade students of MIA and IIS in SMA Muhammadiyah 2 of Pontianak Academic Year 2017/ 2018. The eligibility of the animated media was evaluated by media experts and material experts, meanwhile the ARCS learning motivation (attention, relevance, confidence, and satisfaction) was measured by one-to-one, small group and field test. The results showed that video animation media was very feasible to be used in learning the sub material of Ecosystem Components and Interaction Patterns among Organisms with an average of 4.45 for validation by media experts and 4.47 for validation by material experts. Moreover, the video animation nedua was effective on the generation of learning motivation with an average of 76.53% which was categorized good. Keyword: Development Research, animation media, students’ learning motivation